Evaluation of System of Rice Intensification (SRI) in rice (Oryza sativa) - groundnut (Arachis hypogaea) system under Island ecosystem - DAMODARAN, V; SAREN, B K; RAVISANKAR, N; BOMMAYASAMY, N; SUBRAMANI, T (The Indian Journal of Agricultural Sciences, 2015)
Field experiment was conducted during wet and dry seasons of 2007-09 at Field Crops Research Farm of Central Island Agricultural Research Institute, Port Blair, Andaman and Nicobar Islands to evaluate System of Rice Intensification (SRI) in rice and its residual effect on groundnut in rice (Oryza sativa L.) – groundnut (Arachis hypogaea L.) systems. Time of planting, spacing and nitrogen practices evaluated significantly influenced the yield attributes and yield of rice, while the residual effect of N management practices had a positive influence on the yield attributes and yield of succeeding groundnut. Early planting in second fortnight of June with 20 cm × 20 cm spacing recorded higher panicles/m2 (9.1 %), higher number of filled grains/ panicle (108), higher grain yield (4 678 kg/ha), about 3% higher REY, productivity (26.8 kg/ha/day), and total profitability (` 62 882/ha) compared to the same time of planting with wider spacing (25 cm × 25 cm). Though application of 100% Recommended Dose of Nitrogen (RDN) through urea recorded highest grain yield (4 465 kg/ha) of rice, it was comparable with 50% RDN through Gliricidia + 50% RDN through urea and 75% RDN through Gliricidia + 25% RDN through urea. Application of 50% RDN through Gliricidia + 50% RDN recorded nearly 6% higher REY and ` 6 565/ha more profitability higher output energy in rice-groundnut sequence compared to application of 100% RDN through urea. N management practices of rice, in the crop sequence of rice- groundnut were found to improve the soil nitrogen status. Early planting of rice in second fortnight of June at 20 cm × 20 cm with the application of 50% RDN through Gliricidia + 50% RDN through urea can be recommended for achieving higher productivity, profitability and energy use efficiency of rice - groundnut system in Island ecosystem.